The Effect of Learning with the “Copy the Master Technique” and Learning Motivation on Anecdote Text Writing Skills - Hardianti, Siti; Thahar, Harris Effendi (Universitas Jambi, Indonesia, 2024)
Abstract This research aimed to explain the effect of learning using the Copy the Master technique on the anecdote text writing skills of the tenth-grade students of one senior public school. It was quantitative with experimental research. In addition, this research used a pseudo design and a 2x2 factorial design. The sampling was carried out by using the purposive sampling technique. The research findings show (1) there was an influence of learning using the Copy the Master technique on the anecdote text writing skills of class and (2) there was an influence of learning using the Copy the Master technique on anecdote text writing skills for students with high learning motivation; (3) there was an influence of learning using the Copy the Master technique on anecdote text writing skills for students with low learning motivation. The copy the master technique can be one of the alternative techniques in teaching writing.